Penerapan Algoritma Quick Sort untuk Menyortir Array Berdasarkan Kriteria Tertentu untuk Meningkatkan Efisiensi Komputasi - Nasution, Afifah Naila; Singgam, Pritiy; Al-Hafiz, Ahmad Yusuf; Alvansyah, Oka; Tampubolon, Josua Deo (IAI Nasional Laa Roiba Bogor, 2024)
This research focuses on implementing the Quick Sort algorithm for sorting arrays based on specific criteria, with the aim of increasing computational efficiency in data management. Quick Sort was chosen because of its superiority in sorting data with an average time complexity of O(n log n), making it efficient for use on large datasets. This research applies this algorithm to student data sorted by NIM and name, and considers the grouping of student entry routes. The research results show that the implementation of Quick Sort in sorting student data not only speeds up the data processing process but also allows for more efficient processing in various data conditions.